Impulsive Buying dalam Ekonomi: Studi Perilaku Doom Spending di Indonesia Perspektif Islam - Ardiansyah, Jefri; Ahmad Mansur; Moh. Firdaus Faiz Al’Ula; Abdul Muaz Ali Amri (Universitas Muhammadiyah Prof. DR. HAMKA, 2025)
The rapid development of banking The phenomenon of doom spending has become a trending issue among Indonesian youth. This behavior contradicts Islamic economic principles, such as wasatiyyah (moderation) and qana’ah (contentment), and has negative implications for financial stability and social well-being. This study employs a qualitative method with a phenomenological approach to understand the behavior of doom spending and its implications for Islamic financial management. The findings reveal that doom spending increases the risk of debt, reduces the allocation of wealth for zakat and charity, and undermines the blessings (barakah) of wealth. Contributing factors include emotional pressure from stress or anxiety, the influence of consumerist culture, and the role of social media in promoting materialistic lifestyles. Proposed solutions include enhancing Islamic financial literacy, leveraging financial technology, and strengthening spiritual awareness. These findings underscore the importance of wise wealth management in accordance with Islamic principles to achieve financial balance and a blessed life.